Acoustic scattering of a pair of rigid spheroids based on the T-matrix method - Yang, Yuzheng; Gui, Qiang; Zhang, Yang; Chai, Yingbin; Li, Wei (Frontiers in Physics, 2023)
In this study, the T-matrix method combined with the addition theorems of the spherical basis functions is applied to semi-analytically compute the underwater far-field acoustic scattering of a pair of rigid spheroids with arbitrary incident angles. The involvement of the addition theorems renders the multiple scattering fields of each spheroid to be translated into an identical origin. The accuracy and convergence property of the proposed method are verified and validated. The interference of the specular reflection wave and Franz wave can be spotted from the oscillations of the form function. Furthermore, the propagation paths of the specular reflection and Franz waves are quantitatively analyzed in the time domain with conclusions that the Franz waves reach the observation point subsequent to the specular reflection waves and the time interval between these two wave-series is equal to the time cost of the Franz waves travelling along the sphere surfaces. Finally, the effects of the separation distances, the aspect ratios (the ratio of polar radius to equatorial radius), the non-dimensional frequencies, and the incidence angles of the plane wave on the far-field acoustic scattering of a pair of rigid spheroids are studied by the T-matrix method.